“…we must not hold our fears…” A Case Study exploring the use of Group Dramatherapy as a Therapeutic Intervention with Children and Adolescents Living in Poverty. - Koekemoer, Kaye (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MDram)--University of Stellenbosch, 2006.